Molecular Beam Opto-thermal Study of the Multiple-photon Infrared Excitation of CF3Br. Issue 3 (1985) - Bassi, D.; Boschetti, A.; Iannotta, S.; Scotoni, M.; Zen, M.
Abstract : The multiple-photon excitation (MPE) of CF3 Br has been studied in strictly collisionless conditions by means of the molecular beam optothermal technique. The MPE spectrum shows strong structures which have been attributed to different orders of multiple-photon resonances. The experimental results have been compared with an available theoretical calculation based on the "heat-bath feed-back" model. The effect of the rotational population and of the vibrationally excited "hot bands" on the MPE yield is discussed.